Voluntary wheel running improves molecular and functional deficits in a murine model of facioscapulohumeral muscular dystrophy - Adam J. Bittel; Daniel C. Bittel; Heather Gordish-Dressman; Yi-Wen Chen (iScience, 2024)
Summary: Endurance exercise training is beneficial for skeletal muscle health, but it is unclear if this type of exercise can target or correct the molecular mechanisms of facioscapulohumeral muscular dystrophy (FSHD). Using the FLExDUX4 murine model of FSHD characterized by chronic, low levels of pathological double homeobox protein 4 (DUX4) gene expression, we show that 6 weeks of voluntary, free wheel running improves running performance, strength, mitochondrial function, and sarcolemmal repair capacity, while slowing/reversing skeletal muscle fibrosis. These improvements are associated with restored transcriptional activity of gene networks/pathways regulating actin cytoskeletal signaling, vascular remodeling, inflammation, fibrosis, and muscle mass toward wild-type (WT) levels. However, FLExDUX4 mice exhibit blunted increases in mitochondrial content with training and persistent transcriptional overactivation of hypoxia, inflammatory, angiogenic, and cytoskeletal pathways. These results identify exercise-responsive and non-responsive molecular pathways in FSHD, while providing support for the use of endurance-type exercise as a non-invasive treatment option.